Evaluación de las variedades mejoradas de trigo (Triticum aestivum L.) del INIAP bajo condiciones agroecológicas del campus Salache, UTC 2021 – 2022. - Pogo Moreta, Alexis David (2022)
which is consumed is produced, while 98% is imported, one of the problems is the low productivity of cultivation. This research project was carried out at the Technical University of Cotopaxi - CEASA Campus, with the collaboration of the INIAP Cereal Program, the main objective was to evaluate agro-morphologically 18 improved varieties of wheat (Triticum aestivum L.) originating from INIAP under open field conditions, in order to identify the best varieties that demonstrate a good adaptation and performance for productivity in the study area. A Completely Randomized Block Design was proposed, in a total area of 125 m2, establishing three repetitions each one with 18 treatments in plots of 1 x 1.2 m, providing a total of 54 experimental units. For the evaluation of the variables under study, the methodology proposed by INIAP (2019), called Manual Nº 111, was applied. "Parameters of Evaluation and Selection in Cereals" which allowed evaluating indicators such as; Percentage of emergence, growth habit or size, days of the spike, plant height, type of straw, spike size, number of grains per spike, reaction to diseases, the weight of grains per spike, production, hectoliter or specific weight, type, and color of the grain. In the data analysis of the present investigation, the normality test (Kolmogorov) was generated and it was subjected to a non-parametric Kruskal Wallis analysis of variance. In the case of the variables that are evaluated by means of scales, a table of averages was generated, for data processing, the statistical software InfoStat was used. The results determined that the varieties that presented the best agronomic behavior were: for the performance parameter located in the A range, the INIAP-AMAZONAS 69 variety, with an average production of 6870.37 kg ha-1, for the hectoliter weight indicator, the varieties which are located in the range A were INIAP-IMBABURA 2014 with 75.50 kg hl-1 and INIAP-AMAZONAS 69 with 75.21 kg hl-1, likewise, for the severity parameter, the improved varieties that had the highest level of resistance against yellow rust were INIAP-IMBABURA 2014, INIAP-ATACAZO 69 and INIAP-ALTAR 82 with 0% affectation, for yellow spike rust there are 13 varieties that presented resistance levels (Table. 22), in the case of Fusarium 10 varieties presented resistance (Table. 24) and for yellow dwarf virus three varieties were the most resistant, INIAP-ATACAZO 69, INIAP-COTACACHI 98, INIAP-ZHALAO 2003. With the data obtained, it is concluded that the improved variety for the study area is INIAP-IMBABURA 2014, so it is recommended to continue evaluating this and other improved varieties originating from INIAP, where positive